2013
DOI: 10.5296/ijafr.v3i2.4191
|View full text |Cite
|
Sign up to set email alerts
|

Small-sized companies' earnings management: evidence from Italy

Abstract: This study explores the earnings management practices of small-sized Italian companies. Adopting the earnings distribution approach, it finds that these companies are likely to manage their earnings to achieve two earnings level targets. On the one hand, they manage their earnings to report slightly positive earnings. Those with negative earnings manage them upward to be above the zero threshold. Those with positive earnings manage them downward to bring them close to zero. On the other hand, they manage their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The verification of the statistical significance of the two discontinuities, using the test statistics suggested by Burgstahler and Dichev (1997) and Garrod, Pirkovic, and Valentincic (2006), for which the data is not shown, has revealed that they are statistically significant at a level of 1%. Figure 1 shows that the EM practices are widely popular among Italian private companies, confirming the findings of previous studies (Poli, 2013a(Poli, , 2013b.…”
Section: Sample Selection and Datasupporting
confidence: 87%
See 3 more Smart Citations
“…The verification of the statistical significance of the two discontinuities, using the test statistics suggested by Burgstahler and Dichev (1997) and Garrod, Pirkovic, and Valentincic (2006), for which the data is not shown, has revealed that they are statistically significant at a level of 1%. Figure 1 shows that the EM practices are widely popular among Italian private companies, confirming the findings of previous studies (Poli, 2013a(Poli, , 2013b.…”
Section: Sample Selection and Datasupporting
confidence: 87%
“…6;2015 204 private companies (e.g. Poli, 2013aPoli, , 2013b, whether and how such practices are influenced by ownership structure characteristics have not yet been investigated. Our study, therefore, fills this knowledge gap.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, they may be of poor quality, confirming the findings of previous studies (e.g., Poli, 2012Poli, , 2013aPoli, , 2013bPoli, , 2013c. As a result, they should be interpreted with caution by those who use financial statement information.…”
Section: Resultssupporting
confidence: 88%